IMPLEMENTASI NILAI-NILAI DEMOKRASI PADA PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENINGKATKAN SIKAP DEMOKRATIS SISWA KELAS XI DI SMAN 5 PEKANBARU - M. Fikri Isnan Pramana; Jumili Arianto; Kingkel Panah Grosman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to understand how the implementation of democratic values in Pancasila Education learning can improve democratic attitudes among eleventh-grade students at SMAN 5 Pekanbaru. The background of this research stems from student behavior that shows a lack of democratic attitude, such as not respecting friends' opinions, low tolerance in group discussions, and a tendency to behave individualistically. This research applies a descriptive qualitative approach by gathering data through participant observation, in-depth interviews, and documentation. The informants involved in this study consisted of the vice principal of curriculum, the Pancasila Education teacher, and eleventh-grade students. Data analysis was carried out through the steps of data collection, data reduction, data display, and drawing conclusions, with data validity tested using source and technique triangulation. The results indicated that the implementation of democratic values in Pancasila Education has been carried out using group discussion methods, consensus building (musyawarah), freedom of expression, and habituating mutual respect in class. The teacher functions as a facilitator who creates opportunities for students to participate actively and serves as a model for democratic behavior. Students' democratic attitudes can be seen from their increased courage to express opinions, ability to respect differences, tolerance, and readiness to accept group decisions. Some challenges are still encountered, such as limited learning time, variation in student character, and the lack of active participation from all students in discussions. Overall, the implementation of democratic values contributes positively to enhancing students' democratic attitudes in daily social interaction.